STUDI PERBANDINGAN KUAT TEKAN DAN KUAT LENTUR PADA PERKERASAN JALAN LENTUR DENGAN MENGGUNAKAN AGREGAT KASAR BATU PECAH MESIN DAN BATU ALAMI - Jefri Historisman Waruwu; Tika Ermita Wulandari (Buletin Utama Teknik, 2026)
Road infrastructure requires pavement systems with adequate structural performance to sustain traffic loads and ensure long-term serviceability. This study aims to evaluate the comparative performance of flexible pavement mixtures using machine-crushed aggregates and natural aggregates based on Marshall characteristics, compressive strength, and flexural strength. The research adopts an experimental laboratory method in accordance with Indonesian national standards (Bina Marga specifications) for Asphalt Concrete–Wearing Course (AC-WC) mixtures. Marshall testing was conducted to determine the optimum asphalt content (OAC) and to evaluate key parameters, including stability, flow, density, voids in mineral aggregate (VMA), voids in mix (VIM), and voids filled with bitumen (VFB). In addition, compressive strength and flexural strength tests were performed to assess the mechanical behavior and structural resistance of the asphalt mixtures under load. The results indicate that mixtures incorporating machine-crushed aggregates exhibit higher Marshall stability, improved interlocking, and better load-bearing capacity compared to those using natural aggregates. Furthermore, the compressive and flexural strength values of crushed aggregate mixtures are consistently higher, indicating superior resistance to deformation and cracking. The findings suggest that aggregate type significantly influences the mechanical performance and durability of flexible pavement. The use of machine-crushed aggregates enhances structural integrity, making it more suitable for pavements subjected to moderate to heavy traffic loads. Therefore, proper material selection, accurate determination of OAC, and strict quality control during mix design and production are essential to achieve optimal pavement performance and extend service life.